2020
DOI: 10.1038/s41598-020-61334-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of CD151 as a partner of alpha6 integrin in male germ cells

Abstract: The physiological importance of CD151 tetraspanin is known from somatic cells and its outside-in signalling through integrins was described. In male germ cells, two tetraspanins, CD9 and CD81, are involved in sperm-egg membrane fusion, and similarly to integrins, they occupy characteristic regions. We report here on a newly discovered presence of CD151 in sperm, and present its expression and distribution during spermatogenesis and sperm transition during the acrosome reaction. We traced CD151 gene and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…The equatorial segment (the EqS) of mammalian sperm is the site for sperm-egg fusion initiation, and the organizing center for assembly of molecular complexes required for gamete interaction and fusion. Sperm-egg membrane fusion involves three tetraspanins, CD9 and CD81 and, as lately discovered, also CD151 forming a novel tetraspanin network [ 51 ]. CD151 is highly expressed in the basal layers of cervical mucosa, where epithelial cells come into direct contact with the basement membrane.…”
Section: Epidemiological Association Of Hpv and Reproductive Stages : Hpv-related Male Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The equatorial segment (the EqS) of mammalian sperm is the site for sperm-egg fusion initiation, and the organizing center for assembly of molecular complexes required for gamete interaction and fusion. Sperm-egg membrane fusion involves three tetraspanins, CD9 and CD81 and, as lately discovered, also CD151 forming a novel tetraspanin network [ 51 ]. CD151 is highly expressed in the basal layers of cervical mucosa, where epithelial cells come into direct contact with the basement membrane.…”
Section: Epidemiological Association Of Hpv and Reproductive Stages : Hpv-related Male Infertilitymentioning
confidence: 99%
“…The testicular and epididymal localization pattern is specifically enriched in the EqS as the primary sperm head fusion site. Prior to gamete fusion, CD151 interacts with α6 integrin subunit, which forms a dimer with β4 as a part of cis-protein interactions within sperm [ 51 ].…”
Section: Epidemiological Association Of Hpv and Reproductive Stages : Hpv-related Male Infertilitymentioning
confidence: 99%
“…Studies by van Niel et al [ 71 ] and Chairoungdua et al [ 72 ] indicated that tetraspanins may be crucial players in ESCRT-independent pathways of exosome biogenesis and secretion. It is well known that tetraspanins can modulate membranes by affecting their curvature [ 73 , 74 , 75 , 76 ], which directly predetermines their participation in EV formation. Considering the reversed cone-like molecular shape of CD9, Umeda et al [ 74 ] suggested that clustering of tetraspanin molecules could modulate membrane curvature to enable exosome budding and facilitate subsequent interaction of the C-terminal region of tetraspanins (cytoplasmic tail) with cytoskeletal actin through ezrin, radixin and moesin proteins [ 77 ], which may be involved in EV fission from the parent cell membrane.…”
Section: Role Of Ev Tetraspanins In Somatic Cellsmentioning
confidence: 99%
“…Within the oocyte tetraspanin web, integrins associate with members of the tetraspanin protein family and mediate mutual associations [5,6]. An analogous system is predicted to occur with sperm and CD9, CD81 [7,8], and CD151 [9]. αV integrin is also proposed to be involved in the formation of a multimolecular network [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…An analogous system is predicted to occur with sperm and CD9, CD81 [7,8], and CD151 [9]. αV integrin is also proposed to be involved in the formation of a multimolecular network [7][8][9][10]. The αV integrin recognizes ligands with the arginine-glycine-aspartic Int.…”
Section: Introductionmentioning
confidence: 99%